A 'grafting from' approach to polymer nanorods for pH-triggered intracellular drug delivery. (10th March 2017) - Pelras, Théophile; Duong, Hien T.T.; Kim, Byung J.; Hawkett, Brian S.; Müllner, Markus
Abstract: We report the use of the 'grafting from' approach to produce inherently rod-shaped polymer nanoparticles with triggered drug release. Cylindrical polymer brushes (CPBs) can be directly used to yield functional polymer nanorods for pH-sensitive drug release of doxorubicin (DOX). Water-soluble CPBs have been produced via a straightforward one-step grafting of vinyl benzaldehyde (VBA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) comonomers, in which the VBA distributed throughout the CPBs provides a cost-effective and simple functionality for the subsequent conjugation of DOX using imine chemistry. Atomic force microscopy (AFM) underlined the rod-like conformation of the CPBs prior and after drug conjugation. Fluorescence spectroscopy studies revealed faster drug release in acidic environments (pH 5.0) compared to physiological pH conditions (pH 7.4). Fluorescence lifetime imaging microscopy (FLIM) and in vitro cell studies further highlighted the intracellular DOX release from the CPB drug carriers within MCF-7 breast cancer cells. Graphical abstract: Highlights: Functional polymeric drug carriers are produced via a 'grafting from' copolymerisation. The inherent shape anisotropy of cylindrical polymer brushes offers a simple route to nanorod drug delivery systems. Drug-loaded cylindrical polymer brushes facilitated sustained drug release within breast cancer cells.